Peningkatkan Kompetensi Pengetahuan PLC-SCADA di SMK Nahdlatul Ulama Gresik - Rini Puji Astutik (Universitas Muhammadiyah Palembang, 2024)
The need for SMK graduates is very large for the manufacturing industry, especially in the Gresik area. On the other hand, many SMK are equipped with sophisticated equipment, but the human resources they have are very limited. The technological device required by every industry is a SCADA (Supervisory Control and Data Acquisition) system consisting of a PLC (Programmable Logic Control) and HMI (Human Machine Interface). Mastery of these devices is needed by almost all manufacturing industries so that increasing knowledge competency from PLC-SCADA is very important both for teachers and students and is no exception at SMK Nahdlatul Ulama (NU) Gresik. Through the PLC-SCADA workshop which is an implementation of community service, providing some knowledge to SMK NU students and teachers. The results of this activity show an increase in the knowledge competency of both teachers and students from the observations and questionnaires that have been carried out